Ecoepidemiological evaluation of visceral Leishmaniasis in the Zenu Indigenous community of San Andres de Sotavento, Cordoba: first step for its control - VELEZ-B., IVAN DARIO; TRAVI, BRUNO LUIS; GALLEGO, JORGE; PALMA, GLORIA INÉS; AGUDELO, SONIA DEL PILAR; MONTOYA, JAMES; JARAMILLO, CONSUELO; LLANO, RUBIELA (Revista Colombiana de Entomología, 1995)
During three years (1990-1993), the application of the ecoepidemiological method in the endemic focus of visceral leishmaniasis in the Caribbean coast region of Colombia allowed for the understanding of the mechanism of disease transmission. A new vector for American visceral leishmaniasis was demonstrated: Lutzomyia evansi. It is the main vector in this region. Leishmania infantum (=L. chagasi) is responsible for visceral leishmaniasis as well as cutaneous leishmaniasis. L braziliensis was also found to produce cutaneous lessions. The opossum (Didelphis marsupialis) is an important reservoir for L. infantum (23% infection) and for Tripanosoma cruzi (18% infection). In addition, 25% of dogs showed IFAT (+) for Leishmania. The application of Thornthwaite’s humidity coefficient allowed for the localization of the distribution area for La. evansi and the determination of the limits of the transmission focus (the macro focus). The population dynamics of the vector showed that the rain season (October - December) is the period of higher transmission and that children under three years old are the human population at higher risk. Currently, the first program for the control of visceral leishmaniasis in Colombia is being designed and performed with the aid of these elements.